Pengaruh Minat Belajar dan Kesantunan Berbahasa terhadap Prestasi Penulisan Teks Diskusi Siswa Kelas VIII SMPN 21 Tangerang Selatan - Septiani, Dwi; Aryani; Saragih, Desi Karolina; Maulinda, Rerin (GERAM: Gerakan Aktif Menulis, 2020)
Learning interest is an intellectual system that is very important in learning activities. However, in learning the Indonesian language at the SMP/MTs level, the tendency of students’ learning interest is still weak. One of the learning materials in the curriculum 2013 is discussion text which is the focus of this study. In writing discussion text, one of the obstacles often faced by students was the lack of knowledge about the language politeness in expressing ideas or something disapproval. Related to this problem, this study aimed to explain the effect of learning interest and language politeness towards the writing achievement of discussion text of eight grade students at SMPN 21 South Tangerang. This research method was a survey method with multiple correlation regression analysis. The population of eight grade students of SMPN 21 South Tangerang was 30 students. Then, the data collection was done by distributing questionnaires directly to the sample which were 30 students. To analyze the data, descriptive statistics was used. The results showed; (1) there was an interactive effect between learning interest and language politeness towards the writing achievement of discussion text. It was evidenced by the significant value which was 0.000<0.005 and Fcalculated =34,499. Besides, the learning Interest and language politeness collectively contributed 71.9% towards students’ writing achievement of discussion text; (2) there was an effect of language politeness towards students’ writing achievement of discussion text that was more significant than the effect of learning interest. It can be proven from the value of tcalculated =8,249 for language politeness which was greater than the value of tcalculated =1.762 for learning interest.